PEMBERDAYAAN EKONOMI PETANI GARAM DI KECAMATAN PANGARENGAN KABUPATEN SAMPANG - Rina Nur Azizah; Nur Fathin Luaylik; Muhammad Tijani (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The implementation of community empowerment in improving economic prosperity in Pangarengan village is very unstable and has increased to the maximum. This can be seen from the community's response which is not economically sufficient in Pangarengan village... phenomena that occur in the field are: Lack of counseling or assistance from village officials due to inadequate technological infrastructure and the ability to make salt from traditional to modern methods, the low quality of the salt affects economic welfare of coastal communities. This research aims to Empower Salt Farmers in Improving Economic Welfare in Pangarengan Village, Pangarengan District, Sampang Regency. In this research, Empowerment theory is used according to Wilson (2013:40) with indicators: (1) Awakening (awareness) (2) Understanding (3) Harnessing (Utilization) (4) Using (Use of Skills). The type of research is a qualitative perspective, the data collection technique uses interview and documentation techniques, and the method for determining informants uses a purposive sampling technique of 5 people. Based on the results of this research, it is known that the Empowerment of Pangarengan Salt Farmers in Sampang Regency is said to be quite good. This can be seen from the results of interviews where the author obtained three indicators, namely: Awakening (awareness), Harnessing (Utilization), Using (Use of Skills). However, there are indicators that are still not good, namely: Understanding.